Feasibility and Safety of Laparoscopic Treatment for Early and T3 Stage Gallbladder Cancer: A Systematic Review. Issue 1 (February 2021) - Zhang, Wei; Che, Xu
Abstract : Background: Effect of laparoscopic approach in the treatment of gallbladder cancer (GBC) is still controversial. Materials and Methods: Literature published before December 2019 was retrieved from PubMed, EMBASE, and Cochrane Library databases for a comparative study between laparoscopic group (LG) and open group (OG) for GBC. Revman 5.3 statistical software was used for analysis. Results: Nine comparative studies were eligible and included 654 patients, 287 were in LG and 367 were in OG. Meta-analysis showed that the operation time, estimated blood loss, drainage tube time, and hospitalization time after LG were significantly less than those in the OG [weighted mean difference (WMD)=−27.5; 95% confidence interval (CI), −36.6 to −18.4; P <0.00001; WMD=−267.56, 95% CI, −372.25 to −162.86; P <0.00001; WMD=−1.35; 95% CI, −2.26 to −0.44; P =0.004; WMD=−6.44; 95% CI, −9.07 to −3.81; P <0.00001, respectively). There was no significant difference between LG and OG in postoperative complications, mortality, lymph node dissection, R0 rate, scar recurrence, recurrence, and the 3- and 5-year overall survival (OS) rates. The 1-year OS of all patients, and the 1- and 2-year OS of patients with T3 tumors in the LG were significantly better than those in the OG [relative risk (RR)=1.11; 95% CI, 1.01 to 1.22; P =0.04; RR=1.46; 95% CI, 1.03 to 2.08, P =0.04 and RR=1.71; 95% CI, 1.02 to 2.84; P =0.04, respectively]. Conclusions: The safety and efficacy of LG for early GBC is comparable to OG, and to some extent, it can reduce operation time, estimated blood loss, drainage tube time, and hospitalization time, and have a higher 1-year OS. Patients in T3 stage may have a longer survival by LC, however, this conclusion still needs to be validated by more high-quality clinical studies, especially prospective randomized controlled trials.